MR Imaging Findings of Carcinoma Ex Pleomorphic Adenoma Related to Extracapsular Invasion and Prognosis - Akutsu, A.; Horikoshi, T.; Yokota, H.; Wada, T.; Motoori, K.; Nasu, K.; Yamasaki, K.; Hanazawa, T.; Ikeda, J.-I.; Uno, T. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: MR imaging can reflect the pathologic progression of carcinoma ex pleomorphic adenoma (CXPA). This study aimed to identify the imaging findings related to extracapsular invasion of CXPA. Additionally, the pathologic background of these findings was investigated.MATERIALS AND METHODS: This retrospective study included 37 patients with histologically confirmed CXPA. Three radiologists independently evaluated whether the CXPA showed the following characteristic MR imaging findings: border, capsule, the corona sign on fat-saturated T2WI and contrast-enhanced fat-saturated T1WI, and the black ring sign. The corona sign appeared larger on fat-saturated and/or contrast-enhanced fat-saturated T1WI than on T1WI. The black ring sign was defined as an intratumoral nodule with a thick low-intensity rim on T2WI. Interreader agreement of the visual assessment was performed using κ analysis, and MR imaging and histopathologic findings were also correlated. Kaplan-Meier survival and the log-rank test were used to estimate the 3-year disease-free survival.RESULTS: MR imaging findings, especially peritumoral findings, showed a significant difference between invasive and noninvasive CXPA. The reliability was poor for the border and capsule. In contrast, it was good for the corona sign on fat-saturated and contrast-enhanced fat-saturated T1WI and the black ring sign. Pathologically, the corona sign reflected the invasiveness of the tumor and inflammatory cells, while the black ring sign reflected hyalinization or fibrosis. The corona sign also showed a significant difference in the 3-year disease-free survival.CONCLUSIONS: MR imaging findings, including the corona and black ring signs, reliably differentiated invasive and noninvasive CXPA. The corona sign can be used as a prognostic factor for CXPA.CEcontrast-enhancedCXPAcarcinoma ex pleomorphic adenomaFSfat-saturatedPApleomorphic adenoma